2010
DOI: 10.2174/1874104501004010020
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic Glutamate Receptors: Potential Drug Targets for Psychiatric Disorders

Abstract: Metabotropic glutamate receptors (mGlu receptors) have emerged as new therapeutic targets for psychiatric disorders, such as schizophrenia, depression and anxiety with their regulatory roles in glutamatergic transmissions. To date, several ligands selective for each mGlu receptor have been synthesized, and pharmacological significances of these ligands have been demonstrated in animal models. Among them, mGlu2/3 receptor agonists have been proven to be effective for treating schizophrenia and anxiety disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 122 publications
(148 reference statements)
1
4
0
Order By: Relevance
“…RG7342 represents a novel, potent and selective, orally bioavailable mGlu5 positive allosteric modulator (PAM) which potentiates the activity of glutamate, with a half maximal effective concentration (EC 50 ) of 11.2 nM. In nonclinical behavioural paradigms, RG7342 shows a pro-social, procognitive and antipsychotic drug-like profile, in line with data reported for other mGlu5 PAMs [4,5].…”
Section: Introductionsupporting
confidence: 74%
“…RG7342 represents a novel, potent and selective, orally bioavailable mGlu5 positive allosteric modulator (PAM) which potentiates the activity of glutamate, with a half maximal effective concentration (EC 50 ) of 11.2 nM. In nonclinical behavioural paradigms, RG7342 shows a pro-social, procognitive and antipsychotic drug-like profile, in line with data reported for other mGlu5 PAMs [4,5].…”
Section: Introductionsupporting
confidence: 74%
“…Thus, early pharmacological intervention to improve insulin sensitivity and normalize hyperglycemia helps to overcome type-2 diabetes-related selective neurobehavioral deficits such as depression. Further, glutamate (Widerlov et al, 1988), dopamine (Davis et al, 1991; Dunlop and Nemeroff, 2007), serotonin (Butler and Meegan, 2008) and neuropeptides (Yasuhara and Chaki, 2010) are the dominant mechanisms orchestrating neuropsychiatric disorders. Such alternative mechanisms may contribute to type-2 diabetes-related neurobehavioral deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Pathway-biased and deleterious melatonin receptor mutants have also been reported in an autism spectrum disorder population [4]. Both prospective and retrospective studies have suggested that children who are exposed to valproic acid (2-propylpentanoic acid, VPA) in utero have an increased risk of neuropsychological developmental delays and mood disorder symptoms [5][6][7]; however, the cellular basis for the action of VPA remains elusive.…”
Section: Introductionmentioning
confidence: 99%